Phasic alertness boosts representational momentum - Yan, Junjie; Zeng, Jingwen; Liu, Peiduo (Frontiers in Psychology, 2022)
The final location of a moving object is always misremembered in the direction of the object’s motion; this occurrence is called representational momentum. Three experiments were conducted to investigate the effects of phasic alertness on representational momentum by presenting a visual or auditory warning cue. In experiment 1, the mouse pointer paradigm was used, and the results showed that external warning cues increased forward displacement. Experiment 2 indicated that the effects of phasic alertness and speed of motion on representational momentum were independent. In experiment 3, the probe paradigm was used, and the results showed that external warning cues increased forward displacement as well as participants’ sensitivity to the difference between the target and probe positions. These findings prove that phasic alertness boosts rather than reduces representational momentum. We propose that phasic alertness might influence representational momentum by modulating the process of executive control in the retention interval.